Design and Development of Hybrid Multilevel Inverter employing Dual Reference Modulation Technique for Fuel Cell Applications - R. Seyezhai; Banuparvathy Kalpana (International Journal of Power Electronics and Drive Systems (IJPEDS), 2011)
MultiLevel Inverter (MLI) has been recognized as an attractive topology for high voltage DC-AC conversion. This paper focuses on a new dual reference modulation technique for a hybrid multilevel inverter employing Silicon carbide (SiC) switches for fuel cell applications. The proposed modulation technique employs two reference waveforms and a single inverted sine wave as the carrier waveform. This technique is compared with the conventional dual carrier waveform in terms of output voltage spectral quality and switching losses. An experimental five-level hybrid inverter test rig has been built using SiC switches to implement the proposed algorithm. Gating signals are generated using PIC microcontroller. The performance of the inverter has been analyzed and compared with the result obtained from theory and simulation. Simulation study of Proportional Integral (PI) controller for the inverter employing the proposed modulation strategy has been done in MATLAB/SIMULINK. Keywords: Multilevel inverter, SiC , dual reference modulation, switching losses, PIDOI: http://dx.doi.org/10.11591/ijpeds.v1i2.99